ANALYSIS OF LIFESTYLE, KNOWLEDGE, ATTITUDE, AND KNOWLEDGE OF WOMEN AGED 20-50 YEARS OLD WITH VITAMIN D DEFICIENCY-INSUFFICIENCY IN NORTH SUMATERA, INDONESIA - Keumala, Dina; Zulkarnaini Tala, Zaimah; Lestari, Sri; Hutagalung, Sunna Vyatra; Ganie, Ratna Akbari; Harum, Delina Sekar (Talenta Publisher, 2017)
Background: Study showed that 95% women had serum level of 25(OH)D lower than normal and women have riskier lifestyle than men, this is based on women’s lifestyle, such as avoiding sun rays, sunblock application, low vitamin D intake, and low physical activity. As result of the deficiency, there will be increasing number of metabolic disorders such as obesity and diabetes mellitus type 2.Objectives: To discover lifestyle, knowledge, attitude, and action of women aged 20-50 years old with vitamin D deficiency-insufficiency regarding risk of metabolic disorder caused by vitamin D deficiency.Method: Cross-sectional study engaging 98 women participants with vitamin D deficiency-insufficiency. Lifestyle including avoiding sunlight, low physical activity, and sunblock application were assessed. The scoring was to assess knowledge, attitude and action of women aged 20-50 years old with vitamin D deficiency-insufficiency regarding risk of metabolic disorder in Medan and then the result was analyzed.Result: The study engaged 98 women aged 20-50 years old with vitamin D deficiency-insufficiency, showed vitamin D level with mean 19.66±5.69 ng/ml. There were 95% participants categorized into vitamin D deficiency-insufficiency and 5% participants categorized into vitamin D suficiency. All subjects were found to be low on sun rays exposure, high incidence sunblock applicaton, low vitamin D intake, and low physical activities. According to knowledge about risk of metabolic disorder, there were 42.3% participants with sufficient knowledge and 57.7% with deficient knowledge, and regarding attitude, 48.52% had negative attitude and 51.5% had positive attitude, regarding action, 24.7% was sufficient and 75.3% was deficient. According to the analysis, there was no significant association between action and knowledge, attitude and knowledge, but there was significant association between action and knowledge based on education (p=0.01).Conclusion: Lifestyle, sufficient knowledge, and action could be the caused of low vitamin D level. There was significant association between action and knowledge based on education, but didn’t show any associations. Based on this result, knowledge needs to be improved in order to improve attitude and action with counseling or books that are easy to be understood about the importance of vitamin D